Molecular Techniques for the Study of Hospital Acquired Infection. - Foley, Steven L. (Wiley-Blackwell, 2011)
Providing a broad overview of the microbial pathogens associated with hospital-acquired human illness, Techniques for the Study of Hospital Acquired Infection examines the cost-effective use of laboratory techniques in nosocomial infectious disease epidemiology and control. This concise guide addresses the cost benefits of combining modern molecular techniques with the traditional activities of infection control departments. The book is useful as a guide to hospital infection control programs as well as a text for medical practitioners, grad/medical students, researcher scientists, popu.